2015
DOI: 10.3126/jnps.v35i1.12171
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcome of Neonates Born through Meconium Stained Amniotic Fluid in a Tertiary Hospital of Nepal

Abstract: Introduction: The incidence of meconium aspiration syndrome is still high in the developing world contributing significantly to the neonatal mortality. The study was aimed to know the risk factors contributing to meconium aspiration syndrome and neonatal outcome in a tertiary government hospital of the country.Materials and Methods: It was a hospital based cross sectional study done over a period of three months. All live newborns born through meconium stained liquor were enrolled and all the details regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…2 Gurubacharya SM, in a study based in Nepal found a higher association of PROM in subjects with MSAF. 10 Kumari R et al found MSAF was more common in post term pregnancies and with intrauterine growth restriction (IUGR). 3 Manohar et al in a study published in 2013 concluded that incidence of MSAF was more in pregnancy with crossed EDD (>40 weeks), oligohydroamnios, anemia and preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…2 Gurubacharya SM, in a study based in Nepal found a higher association of PROM in subjects with MSAF. 10 Kumari R et al found MSAF was more common in post term pregnancies and with intrauterine growth restriction (IUGR). 3 Manohar et al in a study published in 2013 concluded that incidence of MSAF was more in pregnancy with crossed EDD (>40 weeks), oligohydroamnios, anemia and preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in Nepal have revealed the incidence of MAS to be 6.6–8.6% and neonatal mortality as high as 11.3% . The incidence of MAS has declined in developed countries due to better obstetric practices and perinatal care; however, challenges remain persistent in the developing countries . Numerous studies have been carried out to identify possible risk factors associated with MAS.…”
mentioning
confidence: 99%
“…Numerous studies have been carried out to identify possible risk factors associated with MAS. Risk factors such as ethnicity, longer gestational age (≥ 42 weeks), caesarean delivery, premature rupture of membranes and nulliparity have been identified …”
mentioning
confidence: 99%
“…The incidence of MAS was high in Nepal with an overall incidence of about 2.0 per 1000 live births. 11 Studies conducted in Nepal have revealed the prevalence of MSAF about 6.5%-14.6%, 8 , 9 , 12 among all live deliveries, the prevalence of MAS among MSAF about 6.6% to 8.6%, 8 , 12 and neonatal mortality from MAS about 5.4% to 11.3%. 8 , 9 , 12 The study conducted in India found the prevalence of MAS among MSAF as 7.7% to 21.5%, 4 - 6 and mortality among MAS as high as 13.8%.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Studies conducted in Nepal have revealed the prevalence of MSAF about 6.5%-14.6%, 8 , 9 , 12 among all live deliveries, the prevalence of MAS among MSAF about 6.6% to 8.6%, 8 , 12 and neonatal mortality from MAS about 5.4% to 11.3%. 8 , 9 , 12 The study conducted in India found the prevalence of MAS among MSAF as 7.7% to 21.5%, 4 - 6 and mortality among MAS as high as 13.8%. 4 - 6 The most common complication of MAS is Respiratory distress and other morbidities were convulsions, sepsis, shock, hypoxic-ischemic encephalopathy, hyperbilirubinemia and hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%